2014
DOI: 10.1111/bcp.12432
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin influences megakaryocytic gene expression leading to up‐regulation of multidrug resistance protein‐4 in human platelets

Abstract: AimThe aim of the study was to investigate whether human megakaryocytic cells have an adaptive response to aspirin treatment, leading to an enhancement of multidrug resistance protein-4 (MRP4) expression in circulating platelets responsible for a reduced aspirin action. We recently found that platelet MRP4 overexpression has a role in reducing aspirin action in patients after by-pass surgery. Aspirin enhances MRP4-mRNA levels in rat liver and drug administration transcriptionally regulates MRP4 gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…33 It has been shown that MRP4 expression and aspirin are linked and that aspirin treatment enhances MRP4 expression by megacaryocytes. 34 In conclusion, our results provide evidence for a novel role of MRP4 in platelet cyclic nucleotide regulation. They also show that MRP4 is not the main transporter responsible for ADP and ATP accumulation in dense granules.…”
Section: Org Fromsupporting
confidence: 51%
“…33 It has been shown that MRP4 expression and aspirin are linked and that aspirin treatment enhances MRP4 expression by megacaryocytes. 34 In conclusion, our results provide evidence for a novel role of MRP4 in platelet cyclic nucleotide regulation. They also show that MRP4 is not the main transporter responsible for ADP and ATP accumulation in dense granules.…”
Section: Org Fromsupporting
confidence: 51%
“…The transcriptional effect on megakaryocytes, responsible for platelet gene expression adaptome , was previously showed, in fact transcriptional change that can be transmitted to circulating platelets is evident for PPARα activation in human bone marrow megakaryocytes 6, 21…”
Section: Resultsmentioning
confidence: 94%
“…To investigate whether aspirin could regulate miR‐21 expression even after in vivo administration and to verify the correlation between MRP4 and miR‐21, we explored miR‐21 expression in platelets obtained from volunteers after aspirin treatment which have aspirin induced MRP4 over‐expression, as previously shown 6, 8…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations